The “Black Box”: How Students Use a Single Search Box to Search for Music Materials - Dougan, Kirstin (Information Technology and Libraries, 2018)
Given the inherent challenges music materials present to systems and searchers (formats, title forms and languages, and the presence of additional metadata such as work numbers and keys), it is reasonable that those searching for music develop distinctive search habits compared to patrons in other subject areas. This study uses transaction log analysis of the music and performing arts module of a library’s federated discovery tool to determine how patrons search for music materials. It also makes a top-level comparison of searches done using other broadly defined subject disciplines’ modules in the same discovery tool. It seeks to determine, to the extent possible, whether users in each group have different search behaviors in this search environment. The study also looks more closely at searches in the music module to identify other search characteristics such as type of search conducted, use of advanced search techniques, and any other patterns of search behavior.